Acceptance of LGBT comics and animation among Public University students in Malaysia - Abdul Rashid, Roswati; Mamat, Roslina; Paee, Rokiah; Hassan, Asmadi; Ismail, Muhd Zulkifli; Ahmad, Normah (Gokmen Arslan, 2022)
Lesbian, gay, bisexual and transgender (LGBT) has always been a sensitive topic in Malaysia, especially among the Malays and Muslims. In terms of morals and religion, LGBT is prohibited and taboo to debate because it can be a sensitive issue to other races and religions. Japanese animation and comics have a specific theme or genre for the LGBT community and its fans. This paper attempts to understand the views of Japanese language students at five Public Universities (UA) who read or watch LGBT-genre Japanese comics and animations. The survey was distributed to the target respondents, and 280 respondents answered the survey. The results of this study are part of the author's research data. The study results showed that 22.5% of the respondents read Japanese comics or animations of the gay or lesbian genre, 19.3% have stopped reading or watching comics or animations of this genre and 58.2% have never read such a genre. The percentage indicates that almost half of the study respondents have been exposed to this negative phenomenon. The objective of this study is to identify lesbian and gay genre comics and animated titles as a community and parental guide. The second objective of this study is to examine the respondents’views so that the public understands why they are involved in such a case.